Prevalence of glucose abnormalities in polycystic ovary syndrome women and evaluating the efficacy of fasting blood glucose in detecting these glucose abnormalities compared to glucose tolerance test - Mohanapu, Swarnalatha; Jayakumar, Abinaya Maathuri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Polycystic ovarian syndrome (PCOS) is the most commonly prevalent endocrinopathy of reproductive age women. It is a significant public health issue with reproductive, metabolic and psychological features. Because patients with PCOS are at high risk for developing glucose abnormalities, the early identification of affected patients and institution of life style changes or pharmacological treatment may help reduce the long-term risks associated with PCOS. This study was done to assess the prevalence of glucose abnormalities and to evaluate the efficacy of Fasting blood glucose (FBG) in detecting glucose abnormalities when compared to 2 hrs oral glucose tolerance test (OGTT). Methods: Hospital based cross sectional study carried out in 300 women diagnosed as PCOS according to Rotterdam criteria. In patients diagnosed as PCOS, Fasting Blood Glucose and OGTT were done. OGTT taken as an accurate test and FBG values compared with OGTT values to evaluate the efficacy of FBG. Prevalence of glucose abnormalities and association with age, BMI and clinical features was evaluated. Results: Glucose abnormalities were detected in 69 (23%) women with 2 hours OGTT, but with FBG only in 49 (16.33%) women, around one third of women were missed. Sensitivity of FBG was 71.01% (95% CI 58.84% to 81.31%). Mean age of women with abnormal OGTT (27.99) was significantly higher than the women with normal OGTT (24.7). Mean BMI of women with abnormal OGTT (27.42) was significantly higher than the Mean BMI of women with normal OGTT (23.36). Conclusions: Sensitivity of FBG was low in detecting glucose abnormalities. Increasing age, increase in a BMI, menstrual abnormalities, hirsutism/acne and family history of diabetes appear to have positive linear correlation with prevalence of glucose abnormalities.